The effectiveness of resilience training and stress management (SMART) on the quality of life in patients with thalassemia major - Babaei MR; Askarizadeh GH; Towhidi A (Zanjan University of Medical Sciences and Health Services, 2017)
Background: Thalassemia is one of the most common genetic diseases in Iran with different physical and psychosocial consequences which affect these patients quality of life . Objectives: The purpose of this study was to investigate the effect of resilience training and stress management on the quality of life in patients with thalassemia major in Kerman-Iran. Methods: In this quasi-experimental study with pre-test and post-test design and a control group, 30 patients referred to Samen-al-Hojaj charity group, were selected by convenience sampling method and randomly divided into two experimental and control groups (each of 15 patients). After completing the pre-test, the experimental group received 10 sessions of training and stress management. Control group received no intervention. The data collection tool was the questionnaire of quality of life (SF-36). Data were analyzed by SPSS software using the covariance analysis. Results: The results of the covariance analysis in the studied variables indicate that the effect of the group (experimental intervention) on the post-test of physical function, general health, the role limitation for physical and emotional health were significant and respectively were (P=0.005 and F=11.22), (P=0.001 and F=16/02) and (P=0.049, F=4.3). However, the effect of the group on the post-test of role limitation for emotional reasons, physical pain, social function, and fatigue or vitality were not significant and respectively were (P=0.20 and F=1.741), (P=0.774 and F=0.085), (P=0.674 and F=0.183 ) and (P=0.288 and F=1.203). Conclusion: According to the results, based on the effectiveness of stress relief and management on some components of the quality of life in patients with thalassemia major, this study can be used to reach an effective solution to improve the quality of life and generally improve the mental status of patients.